The Catalytic Mechanism of Key Enzymes Involved in the Synthesis of Ergothioneine in Lentinula edodes - Zheng Li; Jianjun Ding; Wen Huang; Yinbing Bian; Xi Feng; Ying Liu (Molecules)
C-S lyase is a crucial enzyme responsible for the formation of sulfur-containing flavor compounds in Lentinula edodes. We investigated the involvement of C-S lyase in the synthesis of ergothioneine (EGT) in L. edodes, a high-producing edible mushroom. Through experimental and computational approaches, we identified Lecsl2, a C-S lyase, as a key enzyme involved in EGT synthesis in L. edodes. We characterized the enzymatic catalytic mechanism of Egt1 and Egt2, the two enzymes primarily catalyzing EGT synthesis in fungi. The results showed that Egt1 interacted with His, SAM, and Cys to form the intermediate product Her-sul, while Egt2, a PLP-dependent enzyme, cleaved the C-S bond on Her-sul to produce EGT. However, our findings suggested that Egt2 in L. edodes might not form a covalent bond with PLP, unlike the previously reported catalytic mechanism of Egt2 involving covalent catalysis. The study provided new insights into the synthesis pathway of EGT in L. edodes and highlighted the need for further investigation into the catalytic mechanism of Egt2 in this species.